Finding flaws in the spatial distribution of health workforce and its influential factors: An empirical analysis based on Chinese provincial panel data, 2010–2019 - Bai, Qian; Ke, Xinyu; Huang, Lieyu; Liu, Liming; Xue, Dongmei; Bian, Ying (Frontiers in Public Health, 2022)
We aimed to analyze the health workforce allocation in China from demographic and geographic perspectives simultaneously, then explore the spatial pattern and determinants for health workforce allocation taking account of spillover effect. Health resource density index (HRDI) equals to the geometric mean of health resources per 1,000 persons and per square kilometer. Firstly, the HRDI of licensed physicians (HRDI_P) and registered nurses (HRDI_N) was calculated for descriptive analysis. Global and local Moran’s I indices were employed to explore the spatial features and aggregation clusters of health workforce. Four types of independent variables were selected: supportive resources (bed density, government health expenditure); health care need (proportion of elderly population); socioeconomic factors (urbanization rate, GDP per capita); and sociocultural factors (education expenditure per pupil, park green area), and then spatial panel econometric model was used to assess the direct associations and intra-region spillover effects between independent variables and HRDI_P and HRDI_N. The global Moran’s I index of HRID_P and HRDI_N grew from 0.2136 to 0.2316, 0.1645 to 0.2022, respectively. The local Moran’s I suggested spatial aggregation clusters of HRDI_P and HRDI_N. For HRDI_P, bed density, government health expenditure and GDP had significantly positive associations with local HRDI_P. While proportion of elderly population and education expenditure showed opposite spillover effects. A 1% increase in proportion of elderly population would lead to 0.4098% increase in HRDI_P of neighboring provinces, while a 1% increase in education expenditure leads to 0.2688% decline of neighboring HRDI_P. For HRDI_N, urbanization rate, bed density and government health expenditure exerted significant impacts on local HRDI_N in positive ways. The spillover effect was more evident in urbanization rate, a 1% increase in urbanization rate relating to 0.9080% growth of HRDI_N of surrounding provinces. Negative spillover effects of education expenditure, government health expenditure and elderly proportion were observed on neighboring HRDI_N. There were substantial spatial disparities in health workforce distribution in China; moreover, health workforce showed positive spatial agglomeration with a strengthening tendency in the decade. Besides, supportive resource, health care need, socioeconomic and sociocultural factors, would affect the health labor configure not only in the province itself but also nearby provinces.